Strategies for addressing reading comprehension difficulties in English among Standard Six pupils in Tanzania - Ebby Ngonyani; Rose Ephraim Matete; Johaiven Joel Kashaigili (Освітній вимір, 2025)
This study explored strategies for effectively addressing reading comprehension difficulties among Standard Six pupils in Tanzania. The study was conducted in Kongwa District in Dodoma Region, and data was collected qualitatively from 37 participants, where nine (9) were English teachers, 10 head teachers, eight (8) Ward Education Officers (WEOs), and 10 External School Quality (SQ) assurers. Data was collected through interviews and documentary review. The findings reveal that teachers employed group reading, repeated reading, vocabulary teaching, and guided reading as interactive strategies to enhance pupils' learning comprehension. It was also found that using motivation, appropriate reading materials, technology, assessment and feedback, teaching and learning materials, and using English as the medium of instruction significantly enhances reading comprehension. However, it was found that a lack of a supportive school environment, Internet connectivity, and limited access to English reading materials hindered effective reading comprehension among pupils. It is argued in this study that teachers need to use interactive methods to improve pupils' reading comprehension and fluency in English, and ESQ assurers need to ensure that assessment and feedback are provided to schools. For this to be a reality, the government has to ensure that schools have reading materials, computers, overhead projectors, televisions (TVs), Internet connectivity, and an electrical power supply. Nevertheless, creating conducive and supportive environments at both school and home for pupils to practice the language and providing resources for ESQ assurers remains imperative.